La Educación Ambiental en el desarrollo de actitudes ecológicas - Soplín Isla, Rosita del Carmen (2007)
This bibliographical research studies to environmental education in the development of ecological attitudes in response to environmental problems. Changes in the atmosphere, and the consequences of warming on the planet, further climate change, discrimination in the ozone layer, the effects (on: in which major threats at the level of the entire biosphere as discussed health and others) are constantly discussed. Degradation of vegetation cover, mainly manifested through the destruction of temperate forests due to acid rain and fires. The pollution of inland and marine waters, the inefficient use of water resources in general. The population decline and extinction of many plant and animal species as a result of the alteration and destruction of habitats, with corresponding effects of loss of biodiversity. Given these problems Environmental Education emerges as an alternative solution that seeks to build environmental attitudes f aimed at sustainable development. Which it is a comprehensive, systematic and continuous process of information, training and formal training, formal and informal, based on respect for all forms of life, where people, individually and collectively, become aware and take responsibility for the environment, resources, through the acquisition of knowledge, skills, attitudes, values ​​and motivations that make it easy to understand the complex interrelationships of ecological, social, economic, political, cultural, ethical and aesthetic involved in the environment, as well as participate and mobilized in order to solve and prevent problems and future within a sustainable development process oriented towards coexistence in harmony and balance with nature, for the benefit of present generations to come. In this way the individual through environmental education is achieving assimilate the concepts and internalize the attitudes by which acquired the skills and behaviors that enable you to understand and prosecute the interdependence established between a society. Achieve an overall environmental improvement and sustainable living is possible if among other things individuals perform behaviors referred to as ecological responsible behavior and characterized because they involve behaviors favorable to the environment that contribute to their protection, preservation or at least a reduction environmental deterioration. Ultimately environmental education is a learning process and formation of attitudes that should enable the individual to participate actively and responsibly in their natural and social environment.